A Mini Review of Dolphin Carbohydrate Metabolism and Suggestions for Future Research Using Exhaled Air - Ridgway, Sam (Frontiers in Endocrinology, 2013)
In the 1960s, I explored some aspects of carbohydrate metabolism in healthy bottlenose dolphins (Tursiops truncatus). Their physiological picture resembled what had been described for hyperthyroid diabetics. Dolphins have elevated thyroid hormone turnover, and fasting dolphins maintain a relatively high level of plasma glucose. After dolphins ingest glucose, plasma levels remain high for many hours. Interestingly, plasma glucose must exceed 300 mg/dL (about twice as high as the human threshold) before glucose appears in urine. Due to their diabetes-like states, trainability, and unique natural respiratory anatomy and physiology, dolphins may offer useful clues to metabolites in the breath that may be used to non-invasively monitor diabetes in humans. Dolphins take very rapid and deep breaths that are four or five times as deep as humans and other terrestrial mammals, making them ideal for physiological assessment using non-invasive exhaled air. Avenues for successfully identifying breath-based markers for metabolic disease and physiology in dolphins can be done with both modern technology and the evolutionarily advantageous canine nose. This review summarizes aspects of dolphin metabolism previously learned and offers new directions for diabetes research that may benefit both dolphin and human health.